2006
DOI: 10.1097/01.bpo.0000217714.80233.0b
|View full text |Cite
|
Sign up to set email alerts
|

Salter-Harris I and II Fractures of the Distal Tibia

Abstract: PPC is a common problem following SH type I or II fractures of the distal tibia. Operative treatment may decrease the frequency of PPC in some fractures. Regardless of treatment method, we recommend anatomic reduction to decrease the risk of PPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 26 publications
3
36
0
6
Order By: Relevance
“…These predictors were chosen a priori based on our own hypotheses and previous literature (Rohmiller et al. 2006 , Leary et al. 2009 , Russo et al.…”
Section: Methodsmentioning
confidence: 99%
“…These predictors were chosen a priori based on our own hypotheses and previous literature (Rohmiller et al. 2006 , Leary et al. 2009 , Russo et al.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are many indications that open reduction and internal fixation of deviated fractures greatly reduce the risk of premature closures when compared with conservative therapy 11, 12, 13. Many studies have shown better long-term outcomes in patients treated with anatomical reduction 14, 15, 16…”
Section: Malleolar Fracturesmentioning
confidence: 99%
“…Failure of closed reduction due to interposed periosteum is more common and is more likely in tibial fractures with greater than 20% displacement and where there is an associated fibula fracture [5]. Where the distal tibial epiphysis is involved anatomical reduction is vital to allow timely closure of the physis [7]. In addition, the close proximity of neurovascular structures at this level makes them prone to simultaneous entrapment at the fracture site.…”
Section: Discussionmentioning
confidence: 99%